“Plaster solutions” – Providing support for children residing in emergency housing motels in Hamilton, Aotearoa New Zealand - Bernadine Williams; Linda Murray; Bevan Erueti (Child Protection and Practice)
Since the COVID-19 pandemic, motels have become increasingly used as sites for emergency accommodation in Aotearoa New Zealand. Consequently, children now reside in motel rooms intended for seven day emergency stays for much longer periods of time. Ten key-informant interviews were conducted with service providers supporting children residing in motels in the Waikato region. Thematic analysis generated five themes relating to child wellbeing: 1.) Living conditions, 2.) Physical and psychological safety, 3.) Inappropriateness of existing service models, 4.) Disjointed collaboration between service providers, and 5.) Imagining emergency motels as a “site to build strengths”. The findings suggest the motel environment restricted children’s access to nutrition, safe physical activity and health care. In addition, proximity to adult residents could increase exposure to adverse experiences. Participants suggested creative ways to collaborate and use motel facilities to build family strengths. However ultimately, long stays in emergency housing motels create an environment where systemic barriers to child health, development and education are likely to be entrenched rather than alleviated. Initiatives that significantly reduce the time children spend in motels, and appropriate support for children in these contexts are urgently required to prevent widening health inequities for the “motel generation”.